Internalizing Peer Firm Product Market Concerns: Supply Chain Relations and M&A Activity - AFRIN, FARZANA; KIM, JINHWAN; ROYCHOWDHURY, SUGATA; YOST, BENJAMIN P. (Journal of Accounting Research, 2025)
ABSTRACT We explore whether firms internalize the product market concerns of their economically linked peers by examining merger and acquisition decisions in the context of customer–supplier relations. Given the extensive transfer of capital, knowledge, and information between merging parties, we hypothesize that customers’ competition concerns discourage their suppliers from engaging in vertically conflicted transactions (i.e., acquisitions of their customers’ rivals or suppliers to those rivals). Consistent with our hypothesis, we find that suppliers are less likely to engage in such transactions when their customers are subject to higher product market competition. Moreover, the effect is more pronounced when suppliers and customers have greater relationship‐specific investments and when customers face heightened proprietary information concerns. Using plausibly exogenous variation in common ownership between customers and their rivals as a shock to customers’ competition concerns, we conclude that the link between customers’ competition concerns and supplier acquisitions is likely causal. Our findings suggest that firms alter their investment and strategic decisions in response to the product market competition concerns of their economically related peers.